Exploring complex causal pathways between urban renewal, health and health inequality using a theory-driven realist approach. (January 2015) - Mehdipanah, Roshanak; Manzano, Ana; Borrell, Carme; Malmusi, Davide; Rodriguez-Sanz, Maica; Greenhalgh, Joanne; Muntaner, Carles; Pawson, Ray
Abstract: Introduction : Urban populations are growing and to accommodate these numbers, cities are becoming more involved in urban renewal programs to improve the physical, social and economic conditions in different areas. This paper explores some of the complexities surrounding the link between urban renewal, health and health inequalities using a theory-driven approach.Methods : We focus on an urban renewal initiative implemented in Barcelona, the Neighbourhoods Law, targeting Barcelona's (Spain) most deprived neighbourhoods. We present evidence from two studies on the health evaluation of the Neighbourhoods Law, while drawing from recent urban renewal literature, to follow a four-step process to develop a program theory. We then use two specific urban renewal interventions, the construction of a large central plaza and the repair of streets and sidewalks, to further examine this link.Discussion : In order for urban renewal programs to affect health and health inequality, neighbours must use and adapt to the changes produced by the intervention. However, there exist barriers that can result in negative outcomes including factors such as accessibility, safety and security.Conclusion : This paper provides a different perspective to the field that is largely dominated by traditional quantitative studies that are not always able to address the complexities such interventions provide. Furthermore, the framework and discussions serve as a guide for future research, policy development and evaluation. Highlights: Urban renewal programs can affect health and health equity. We present some of the pathways linking urban renewal programs and health. Realist evaluation, a theory-driven approach was used to discuss potential causal pathways. Mechanisms linking public spaces and street repairs to health are discussed.